2005
DOI: 10.1007/s10327-005-0193-4
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity analysis of a soybean isolate of Mungbean yellow mosaic India virus by agroinoculation

Abstract: Yellow mosaic disease (YMD) of legumes endemic to South Asia are caused by begomoviruses transmitted by whiteflies. Based on molecular characterization, two distinct viruses -Mungbean yellow mosaic India virus (MYMIV) and Mungbean yellow mosaic virus (MYMV) -were found previously to be the etiological agents of YMD in legumes. Here, host range studies with a soybean isolate of MYMIV (MYMIV-[Sb]) were carried out by both whitefly transmission and agroinoculation. MYMIV-[Sb] was similar to a cowpea isolate of MY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Agroinoculation, a technique developed by Grimsley et al [18] and PCR based expression analysis of coat protein (CP) gene expression showed higher expression in flowering stages of the crop. Our results were in accordance with the reports of Usharani et al [53]. Practical symptomology and coat protein expression may vary because symptom appears after the preliminary multiplication of the viral particles, but the coat protein expression reveals even a slighter viral residue in a plant.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Agroinoculation, a technique developed by Grimsley et al [18] and PCR based expression analysis of coat protein (CP) gene expression showed higher expression in flowering stages of the crop. Our results were in accordance with the reports of Usharani et al [53]. Practical symptomology and coat protein expression may vary because symptom appears after the preliminary multiplication of the viral particles, but the coat protein expression reveals even a slighter viral residue in a plant.…”
Section: Discussionsupporting
confidence: 95%
“…S3). These results were in accordance with the reports of Usharani et al [53]. Intensity of infection was more during the flowering phase when compared with germination and vegetative phase.…”
Section: Disease and Its Confirmationsupporting
confidence: 95%
“…The genetic isolation shown by them makes it an interesting object to study. The genetic isolation may probably arise because they infect only legume hosts especially blackgram and mungbean which are not [16,19]; mungbean isolate [23]; cowpea isolate [24]; soybean isolate [25], and for blackgram isolate of MYMV [26]). Infection of MYMV in cowpea has not been examined so far.…”
Section: Discussionmentioning
confidence: 99%
“…Based on sequence identity analysis, yellow mosaic virus isolates of grain legumes are differentiated into four species, viz: Mungbean yellow mosaic India virus (MYMIV), Mungbean yellow mosaic virus (MYMV), Dolichos yellow mosaic virus (DYMV) and Horsegram yellow mosaic virus (HgYMV). Of these MYMIV and MYMV are most important, MYMIV is more predominant in northern, central and eastern regions of India [4] and MYMV in southern [5,6] and western regions. These virus species belong to the genus Begomovirus of the family Geminiviridae.…”
Section: Introductionmentioning
confidence: 99%
“…It is especially a major challenge in India where grain legumes are important constituents of vegetarian diet. Phylogeographic analysis of YMV characterized, led to recognition of totally seven different YMV species, viz., Mungbean yellow mosaic India virus (MYMIV; [5]), Mungbean yellow mosaic virus (MYMV; [6]), Horsegram yellow mosaic virus (HgYMV; [7]), and Dolichos yellow mosaic virus (DoYMV; [8]). Recently, Velvet bean severe mosaic virus (VBSMV; FN543425) has been described from the Himalayan foothills.…”
Section: Introductionmentioning
confidence: 99%